Internalisasi Nilai-Nilai Islam dalam Kultur Sekolah: Pendekatan PAl Berbasis Proyek - Husnul Khotimah; Fauziana Ulfi; Gusmaneli (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Islamic Religious Education (PAI) in schools holds a strategic function in shaping students’ Islamic character, which is closely related to the internalization of values through daily educational culture. Character formation is not limited to cognitive understanding of religious teachings, but is strengthened through habitual practice, social interaction, and reflective experience within the school environment. Project-Based Learning (PjBL) offers a relevant approach for encouraging value embodiment, as it provides meaningful learning activities that connect religious concepts with real-life applications. Collaborative projects, such as social service initiatives, environmental care movements, or mosque stewardship programs, facilitate the development of empathy, responsibility, and spiritual awareness. The internalization process becomes more effective when supported by a school culture that consistently displays Islamic values through teacher role modelling, institutional policies, and participatory student activities. Therefore, strengthening Islamic character requires the integration of PjBL with school-wide cultural practices, collaborative educational relationships, and continuity between school and family environments, forming a comprehensive ecosystem of value education.